Development of a Safe and Smart Sensor for Medical Center Environments - Ibrahim, Anas Abdel Hamid Abdel Majeed; Hussein, Ali Abdul Wahab Karim (American Journal of Botany and Bioengineering, 2025)
In this study, an IoT-based, smart healthcare monitoring system has been developed to monitor patients' basic health signs and room conditions in real-time. This system can relay information about room temperature, heart rate, and carbon dioxide and monoxide presence in a room. It can simultaneously monitor the vital signs of multiple patients. In case of any abnormalities in either of the sources, the concerned medical team will be alerted continuously until the error is resolved by recalibrating the sensor. The monitoring unit can be implemented either in hospital environments or in-house medical treatment. The whole scheme works properly, with minimal power consumption and negligible error in data gathering when the prototype is experimented with . The concept of smart buildings has emerged rapidly over the last few decades, and smart buildings are being embraced by developed countries worldwide. However, until recently, developing countries were still stuck with traditional buildings and environments. With the proliferation of various modern devices and the recent trend of global automation, developed countries are advancing towards keeping their environments non-redundant and safe for people. Smart buildings can include homes, offices; shopping malls, hospitals; and other excessive public buildings that can gather information about their environment using various sensors and thereafter take appropriate actions automatically, with minimal human involvement, which makes such buildings smart when compared to ordinary buildings.